P–T–t evolution of eclogite/blueschist facies metamorphism in Alanya Massif: time and space relations with HP event in Bitlis Massif, Turkey - Çetinkaplan, M.; Pourteau, Amaury; Candan, O.; Koralay, O.; Oberhänsli, R.; Okay, A.; Chen, F.; Kozlu, H.; Sengün, F. (2016)
© 2014, Springer-Verlag Berlin Heidelberg. The Alanya Massif, which is located to the south of central Taurides in Turkey, presents a typical nappe pile consisting of thrust sheets with contrasting metamorphic histories. In two thrust sheets, Sugözü and Gündogmus nappes, HP metamorphism under eclogite (550–567 °C/14–18 kbar) and blueschist facies (435–480 °C/11–13 kbar) conditions have been recognized, respectively. Whereas the rest of the Massif underwent MP metamorphism under greenschist to amphibolite facies (525–555 °C/6.5–7.5 kbar) conditions. Eclogite facies metamorphism in Sugözü nappe, which consists of homogeneous garnet–glaucophane–phengite schists with eclogite lenses is dated at 84.8 ± 0.8, 84.7 ± 1.5 and 82 ± 3 Ma (Santonian–Campanian) by 40Ar/39Ar phengite, U/Pb zircon and rutile dating methods, respectively. Similarly, phengites in Gündogmus nappe representing an accretionary complex yield 82–80 Ma (Campanian) ages for blueschist facies metamorphism. During the exhumation, the retrograde overprint of the HP units under greenschist–amphibolite facies conditions and tectonic juxtaposition with the Barrovian units occurred during Campanian (75–78 Ma). Petrological and geochronological data clearly indicate a similar Late Cretaceous tectonometamorphic evolution for both Alanya (84–75 Ma) and Bitlis (84–72 Ma) Massifs. They form part of a single continental sliver (Alanya–Bitlis microcontinent), which was rifted from the southern part of the Anatolide–Tauride platform. The P–T–t coherence between two Massifs suggests that both Massifs have been derived from the closure of the same ocean (Alanya–Bitlis Ocean) located to the south of the Anatolide–Tauride block by a northward subduction. The boundary separating the autochthonous Tauride platform to the north from both the Alanya and Bitlis Massifs to the south represents a suture zone, the Pamphylian–Alanya–Bitlis suture.